Parameteranalyse eines redundanten Roboters mit Pivotpunkt-Restriktion - Hutzl, Jessica (KIT Scientific Publishing, 2017)
Nowadays robots are used not only in production lines, but also in the field of medicine. In this thesis an analysis was performed which relates to a serial, redundant robot and its parameters. The pivot point restriction results from the minimally invasive surgical scenario. The parameter analysis evaluates the robot performance by indicators, which depend on the selected parameters and the operating area.